Практичні аспекти формування облікової політики бюджетних установ - Сліпенчук, Г. В.; Соловей, Н. В. (Ways to Improve Construction Efficiency, 2014)
The paper deals with aspects of the formation of accounting policies for public institutions with regard to their legal support. Proposed sections that should be considered when developing an order on accounting policies.